Effect of surface roughness on fatigue life - Ahmad Kamil, Miskam (2010)
The main purpose of this project is to determine the effect of surface roughness on fatigue life for Mild steel specimen. The study of fatigue life and effect of surface roughness is very important in order to minimize the cost of machining and time of machining and also to study the durability of materials. The influence of machined surface roughness on the fatigue life of Mild steel has been investigated. Fifth teen bending fatigue specimens have been machined according to various machining roughness conditions and tested in fatigue test. In order to explain the effect of surface roughness, S-N curves has been plotted to express the test results. After the fatigue test has been completed, the surface fractures are analyzed to ensure that the specimens are failed due to fatigue. Based on the examination, the Mild steel specimen was failed due to transgranular manners and the failure surfaces consist of two region which is crack propagation region and rapid fracture region.